2018
DOI: 10.1111/ddi.12710
|View full text |Cite
|
Sign up to set email alerts
|

Gone with the forest: Assessing global woodpecker conservation from land use patterns

Abstract: Aim As a result of their ecological traits, woodpeckers (Picidae, Aves) are highly sensitive to forest cover change. We explored the current land cover in areas of high species richness of woodpeckers to determinate regions where urgent conservation actions are needed. In addition, we identified woodpecker species that are sensitive to forest loss and that have high levels of human habitat modification and low levels of protection (through protected areas) in their distribution ranges. Location Global. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
0
10
0
2
Order By: Relevance
“…We find something similar in the largely tropical Oriental region, which may be the result of the specific characteristics of the forests or avifaunal communities in this region (e.g. it is a hotspot for woodpeckers [55]) but may also be influenced by the fact that there is less mature forest left in this region than in other tropical regions (see [56] for brief synopsis). The loss of mature forest reduces the availability of substrates (e.g.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We find something similar in the largely tropical Oriental region, which may be the result of the specific characteristics of the forests or avifaunal communities in this region (e.g. it is a hotspot for woodpeckers [55]) but may also be influenced by the fact that there is less mature forest left in this region than in other tropical regions (see [56] for brief synopsis). The loss of mature forest reduces the availability of substrates (e.g.…”
Section: Discussionmentioning
confidence: 64%
“…improving the retention of large trees). A comprehensive study of all forest birds in some regions like the Amazon or Congo Basin (where, notably, there are hotspots of woodpecker richness [ 55 ]) would require considerable local expertise and training, which is often difficult to achieve due to social and monetary limitations. Thus, we conclude, excavators have excellent potential as study subjects for conservation monitoring and planning initiatives (see also [ 61 ] with regard to woodpecker conservation itself) and to guide the establishment of region-wide forest conservation strategies, especially in the largely understudied tropical regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The piedmont forest of NW Argentina is currently subject to a very intense selective forest extraction with little or no planning designed to ensure the maintenance of the forest's economic and ecological value (Grau & Brown 2000, Pacheco & Brown 2006. Thus, it is necessary to understand the resource requirements of primary excavating birds and to develop forest management schemes to ensure the conservation of these species, particularly of woodpeckers, which are very sensitive to environmental change due to their specific ecological requirements (Ojeda & Chazarreta 2014, Vergara-Tabares et al 2018. Despite the studies carried out in the last decade in these forests (Politi et al 2009, Albanesi et al 2016, Ruggera et al 2016, further specific studies of tree use need to be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that woodpecker species can have similar or different drumming types [24][25][26][27] . Furthermore, many researches have reported that species richness and behaviour of woodpecker are strongly in uenced by tree availability and landscape 19,20,21 . Therefore, more variations of drumming types may be discovered, even within species, using observational studies.…”
mentioning
confidence: 99%